The Role of Management Information Systems in Decision Making of The Principal in SMA Negeri 14 Bekasi City - Arasy, Lizwar Mughni; Baharuddin (Proceeding International Conference on Education, 2023)
The purpose of this study is to explain the role of management information systems for school principals in decision making at SMA Negeri 14 Bekasi. The main problem in this thesis is how the role of the management information system in SMA Negeri 14 Bekasi City is. The focus of the problem in this study is how the components of management information systems and how the role of information systems in decision making in SMA Negeri 14 Bekasi City. The research method that the author uses in conducting this research is descriptive qualitative analysis where the author describes and analyzes the data obtained in the field. Data collection techniques were carried out through interviews, observations, and document studies. From the research conducted, the authors get the results that the education management information system for school principals in decision making has played a role. It can be observed that the principal in making decisions uses data and information obtained from the management information system at SMA Negeri 14 Bekasi City.